(untitled) (Educational Dimension, 2022)
The importance of modern schools in developing students’ problem-solving skills, including through digital tools, is described in the article, which includes the development of basic coding skills and digital literacy, as well as the ability to solve problems and make decisions based on planning and analysis of situations. Computational thinking (CT) is built on the foundation of these abilities. The authors contend that the employment of specialized digital tools promotes the development of computational thinking and that purposeful creation of computational thinking improves teachers’ and students’ digital competence. The concept of CT, as well as existing definitions and components, are examined in this article. A list of courses from various countries’ curriculum on which CT is studied in primary school is provided. The importance of CT as a fundamental talent for everyone is underlined, and it should be developed through the integration of several disciplines to solve problems. The link between the CT components and the key competencies that should be instilled in kids as part of the primary education curriculum. The findings of a survey of more than 60 primary school teachers from various regions of Ukraine about their understanding of the concept of computational thinking and their experience in the development of skills related to all components of computational thinking in primary school students are presented. A review of open educational resources from around the world is offered to assist teachers in enhancing students’ CT skills. The strategy for putting the CT development concept into practice for future teachers and primary school teachers is offered, taking into account the ability to employ specific digital tools.